2015
DOI: 10.1111/jcmm.12422
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic effect of statins on nephrogenic diabetes insipidus

Abstract: Statins competitively inhibit hepatic 3-hydroxy-3-methylglutaryl-coenzyme A reductase, resulting in reduced plasma total and low-density lipoprotein cholesterol levels. Recently, it has been shown that statins exert additional ‘pleiotropic’ effects by increasing expression levels of the membrane water channels aquaporin 2 (AQP2). AQP2 is localized mainly in the kidney and plays a critical role in determining cellular water content. This additional effect is independent of cholesterol homoeostasis, and depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 259 publications
(336 reference statements)
1
26
0
Order By: Relevance
“…36 Of all patients taking lithium, up to 55% of the patients report various degrees of NDI, requiring them to make major lifestyle modifications, including continuous access to water and frequent voiding to avoid hydronephrosis and bladder dilation/dysfunction. 10 This complication can significantly affect quality of life and add substantial burdens to these psychologically compromised populations. Dysregulation of AQPs in the collecting duct is a crucial mechanism for the development of lithium-induced NDI, but the exact mechanism of how lithium causes NDI is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Of all patients taking lithium, up to 55% of the patients report various degrees of NDI, requiring them to make major lifestyle modifications, including continuous access to water and frequent voiding to avoid hydronephrosis and bladder dilation/dysfunction. 10 This complication can significantly affect quality of life and add substantial burdens to these psychologically compromised populations. Dysregulation of AQPs in the collecting duct is a crucial mechanism for the development of lithium-induced NDI, but the exact mechanism of how lithium causes NDI is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…50 Some of these potential therapeutic strategies included activating the cAMP pathway using calcitonin to increase cAMP levels via GaS activation, 11 stimulating the nitric oxide/cGMP pathway with the phosphodiesterase inhibitor sildenafil, 13,51 affecting the PGE2 pathway using the COX-2 inhibitor celecoxib, 52,53 or modulating the actin cytoskeleton network with statins to decrease AQP2 endocytosis. 9,10 These approaches seem promising, but perhaps because lithium exerts such a complex effect on AQP2 trafficking and collecting duct morphology, none of them have yet been shown to provide sustainable benefits in patients. .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was in line with the diagnostic criteria and classification of diabetes of World Health Organization (WHO) in 1999 [13]. All the patients were subjected to a detailed medical examination and fundus ophthalmoscope examination by using a Canon non-mydriasis retinal camera (Canon, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Hyperlipidaemia is an important atherogenic factor by promoting the formation and accumulation of lipid plaques in the arteries . Currently, statins are the leading lipid‐lowering drugs that inhibit 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase, the rate‐limiting enzyme for de novo synthesis of cholesterol . However, increasing numbers of studies have reported side effects of statins .…”
Section: Introductionmentioning
confidence: 99%